Extreme Claims in Advertisements & Consumer Attitudes: The Influence of Consumer Knowledge & Country-of-Origin (Gyan Management Journal, 2008)
The paper suggests a model of consumer attitude formation resulting from evaluation of claims and extreme claims in advertisements as moderated by the consumer's perception of products and their country of origin. The attitude formation is a result of evaluation of advertisement claims and that in turn is moderated by the consumer's prior knowledge and his involvement with the product category or product class. The paper proposes that every consumer has a credibility threshold which is function of consumer's involvement, prior experience with the product category, consumption of the product or any in its category, prior experience with the product class, perception about the country of origin, credibility of the media involved.
Keywords: Advertisements; Consumer Attitudes; Influence; Consumer Knowledge; Country-of-Origin